Study of Rotating and Jet Plasma Treatments on Surface Wettability of Glass - Berczeli, Miklós; Weltsch, Zoltán (International Journal of Engineering and Management Sciences, 2025)
This work investigates the wettability properties of a glass surfaces by using atmospheric pressure cold plasma systems. Treatments were performed by using a rotating-head unit and a jet-type torch during the plazma treatments. The nozzle-to-surface distance (8–15 mm) and the feed rate (50–400 mm/s) were modifying. The untreated glass showed limited wetting, with average water and ethylene glycol contact angles (WCA and EGCA) of 64.7° ± 1.8° and 45.2° ± 1.5°, respectively. After plasma treatment, both systems showed clear improvements, although their efficiency profiles were different. Using the rotating plasma head at 8 mm and 100 mm/s speeds, the WCA decreased to 9.3° ± 0.8°, indicating almost complete wetting. Jet plasma achieved similar results (WCA = 14.1° ± 1.2°), but slightly less uniformly. Changes in wettability were closely related to the exposure time determined by the feed rate: slower movement increased activation, while overexposure occasionally resulted in small thermally induced surface marks that were visible under an optical microscope. As the results showed the rotating plasma reached more homogeneous activation, while the jet system provided stronger local effects at a lower energy input. Based on these results the atmospheric plasma is effective in increasing the surface energy. Rotating systems appear to be advantageous for large, flat areas, while jet plasma is better suited for localized surface modification aimed at improving adhesion or coating performance.